IMPLEMENTASI DAN EVALUASI MANAJEMEN KONFLIK DALAM LINGKUNGAN PENDIDIKAN (STUDI KASUS DESKRIPTIF KUALITATIF DI MADRASAH IBTIDAIYAH CIKARANG UTARA) - Ira Haryani; Sri Utaminingsih; Nuryati Djihadah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the implementation and evaluation of conflict management in the educational environment at MI Al-Muslimin North Cikarang. The focus of the study includes the implementation and evaluation of conflict management in the educational environment. The research is motivated by the fact that conflict is part of the dynamics of educational organizations that require appropriate management to prevent hindering the achievement of educational goals. The study uses a qualitative approach with a descriptive case study method. The research informants numbered 13 people consisting of the madrasah principal, vice-principal, teachers, and education staff selected through purposive sampling techniques. Data collection was conducted through in-depth interviews, observation, and documentation studies. Data validity was obtained through triangulation of sources, techniques, and time. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of conflict management is carried out through problem identification, open communication, clarification, deliberation, joint decision-making, and follow-up on conflict resolution. Conflicts that occur are generally caused by differences in perception, communication, coordination, and division of tasks. Conflict management evaluation is carried out periodically through an evaluation forum involving all elements of the madrasah. The evaluation results demonstrated improved communication, coordination, working relationships, and task implementation effectiveness. The study concluded that the implementation and evaluation of conflict management at MI Al-Muslimin North Cikarang supported the creation of effective, collaborative, and adaptive madrasah governance, oriented toward continuous improvement in educational quality.